Factorisation

Lesson

Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x+a\right)\left(x+b\right)$`y`=(`x`+`a`)(`x`+`b`).

$y=x^2+4x+3$`y`=`x`2+4`x`+3

Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x-a\right)\left(x-b\right)$`y`=(`x`−`a`)(`x`−`b`).

$y=x^2-11x+28$`y`=`x`2−11`x`+28

Factorise the quadratic using the method of completing the square to get it into the form $y=\left(x+a+\sqrt{b}\right)\left(x+a-\sqrt{b}\right)$`y`=(`x`+`a`+√`b`)(`x`+`a`−√`b`).

$y=x^2+8x+14$`y`=`x`2+8`x`+14